Sanksi Pidana terhadap Pejabat Negara yang Melakukan Korupsi atas Penyalahgunaan Wewenang - I Gede Sayogaramasatya; I Made Minggu Widyantara; Ida Ayu Putu Widiati (Jurnal Interpretasi Hukum, 2021)
The large number of state officials who commit corruption due to abuse of authority while exercising their authority can lead to losses to State finances. This study aims to determine the regulation of corruption by state officials in Indonesia, as well as to determine the sanctions for state officials who commit corruption for abuse of power. The research method used in this research is normative legal research with a statutory approach. The results showed that the regulation of corruption committed by state officials in the Corruption Eradication Law No. 20 of 2001, which defines that the act is committed by everyone against the law only to enrich himself or others including corporations which categorized as causing financial losses to the country's economy. There are two sanctions for officials who commit corruption for abuse of office, namely the death penalty and imprisonment.